New insight into the molecular control of bacterial functional amyloids - Taylor, Jonathan D.; Matthews, Steve J. (Frontiers in Cellular and Infection Microbiology, 2015)
Amyloid protein structure has been discovered in a variety of functional or pathogenic contexts. What distinguishes the former from the latter is that functional amyloid systems possess dedicated molecular control systems that determine the timing, location, and structure of the fibers. Failure to guide this process can result in cytotoxicity, as observed in several pathologies like Alzheimer's and Parkinson's Disease. Many gram-negative bacteria produce an extracellular amyloid fiber known as curli via a multi-component secretion system. During this process, aggregation-prone, semi-folded curli subunits have to cross the periplasm and outer-membrane and self-assemble into surface-attached fibers. Two recent breakthroughs have provided molecular details regarding periplasmic chaperoning and subunit secretion. This review offers a combined perspective on these first mechanistic insights into the curli system.